SURVEY AND POPULATION DENSITY EVALUATION OF OLIVE TREES MITES WITH APPLICATION OF SOME INTEGRATED CONTROL OF MITES PESTS - Mohammed M. E. Elmoghazy; Haifa A. S. Alhaithloul (Journal of Animal and Plant Sciences, 2023)
Numerous mite species frequently affect olive trees worldwide; phytophagous mites induce damage to leaves, buds, and fruits. This research work was conducted as an exploratory assessment of the mite fauna of olive trees, its population prevalence, and the composition of control strategies by comparing the efficacy of predation of Amblyseius swirskii with acaricide Danisaraba 20% SC (active constituent cyflumetofen) for control of pest mites on olive trees in the open field. Results showed that 12 species from 11 genera belonging to 6 families were identified. Six species were identified as a new record for Aljouf region, Saudi Arabia. Eriophyid mites were the most prevalent phytophagous species associated with olive aerial parts.The temperature and relative humidity in various months significantly influence mites' activity and population density. At an average temperature of 20 to 40 °C and 12 to 30% rh, the population density of mites began to rise at the beginning of March and peaked in June. Comparison of predation of A. swirskii with acaricide Danisaraba 20% SC in field revealed that the enumeration of different stages of pest mites started declining gradually. The Eriophyid population recorded the lowest number on the 48th day after the second release of A. swirskii at a predator/prey ratio of 1:7. While population steadily increased on the 16th day after the second launch of the acaricide Danisaraba. A. swirskii has proved to be a promising candidate for biological control of olive trees mites compared with acaricide Danisaraba 20% SC in an open field.
Keywords: Olive mite; survey; Amblyseius swirskii; acaricide; integrated control